Technical report on a time-motion analysis of male judo cadets` combats between weight divisions - Miarka, B.; Perez, D. I. V.; Aedo-Munoz, E.; Fernandes da Costa, L. O.; Barreto, L. B. M.; Brito, C. J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Methods. Time-motion analysis data of cadet-athletes (age: 15.95+/-0.68 years-old) were grouped by weight divisions, according to the following criteria: lightweight Lighters (n = 224 combats of -50kg, -55kg and -60kg), middleweight Middlers (n = 76 combats of -66kg, -73kg and -81kg) and heavyweight Heavies (n = 50 combats of -90kg and +90kg) at four state judo championships. Total and sequential time-motion analyses were observed, according to each combat phase (i.e. standing combat, approach, gripping, attack, groundwork combat, and pause phases) and compared by weight divisions, p<=0.05. Results. The main results indicated significant differences between combat time, with lightweight Lighters (234.4s +/- 122.3s) > middleweight Middlers (191.6s +/- 118.2s) and heavyweight competitors Heavies (176.8s +/- 131s), standing combat time, with Lighters (125.4s +/- 67.4s) > Middlers (99.6s +/-70.8s) and Heavies (91.1s +/- 63.6s), approach phase, with Lighters (41.5s +/- 26s) > Middlers (27.2s +/- 18.2s) and gripping phase, with Lighters (75.5s +/- 49.2s) > Heavies (51.3s +/- 36.9s). Conclusions. Our results suggest that individual training programs should be adjusted for cadets according to their weight divisions with consideration given to the temporal structure of the competitive environment.